END-TIDAL CO2 DETECTION DURING CADAVERIC VENTILATION. Issue 12 (23rd November 2015) - Coats, T; Biggs, M; Robinson, C; Rutty, G; Adnan, A; Morgan, B
Abstract : Objectives & Background: "Life like" end-tidal CO2 production has been reported in frozen cadaver during intubation training. There is currently no human model of CPR, however the new technique of post-mortem CT (PMCT) uses CPR to circulate injected contrast for an enhanced CT scan to aid the diagnosis of the cause of death. This might give the potential to compare different methods of CPR. This procedure also allowed us to examine ETCO2 production, to see if the previous single observation could be reproduced. Methods: The patient was an elderly female without known abnormality of the airway, who had been in a temperature-controlled environment at 4 degrees centigrade for 32 hours after death with no other preservation. She was intubated and approximately 60 minutes later ventilation was commenced. End-tidal CO2 was measured from the start of ventilation using continuous waveform capnography (Propaq CS Monitor, Model 246, Software version 3.7X, Welch Allyn). After eight minutes of ventilation a right ante-cubital venous injection of contrast was given and two minutes of chest compressions performed using a Lucas device. Ventilation was then stopped on an inspiratory hold and a whole body CT was undertaken. The project had Research Ethics Committee approval and was supported by a Resuscitation Council (UK) grant. Consent was obtained from relatives. Results: The initial ETCO2 levels were high (6kPa), then decreased rapidly confirming previous findings. A novel observation was that the level of CO2 rose again (albeit at low levels) when CPR was started, presumably due to effective circulation. The post-mortem CT confirmed circulation had been achieved, as contrast was seen in the pulmonary vessels, and also confirmed that the endotracheal tube placement. A further novel finding was that end-tidal CO2 was again higher after the pause in ventilation required for the CT scan, presumably due to diffusion of CO2 down a concentration gradient created by the ventilation-induced fall in alveolar partial pressure. Conclusion: This initial case suggests that end-tidal CO2 in cadavers might have a role; (a) in a protocol for post-mortem CT (as it may indicate effective ventilation and circulation of contrast), or (b) in the comparison of the effectiveness of different methods of CPRFigure 1 .